Assessment of Carotid Plaque Stability Using Contrast-Enhanced Ultrasound and Its Correlation With the Expression of CD147 and MMP-9 in the Plaque - Shanshan Huang (Frontiers Media S.A., 2021)
This study aims to investigate the correlation between the enhancement degree of contrast-enhanced ultrasound (CEUS) and the expression of CD147 and MMP-9 in carotid atherosclerotic plaques in patients with carotid endarterectomy and evaluate the diagnostic efficacy of CEUS using pathological results as the gold standard. Thirty-eight patients who underwent carotid endarterectomy (CEA) for carotid stenosis in the Department of Neurovascular Surgery of the Second People’s Hospital of Shenzhen from July 2019 to June 2020 were selected. Preoperatively, two-dimensional (2D) ultrasound scan was performed on all patients to assess the characteristics of the plaque and degree of stenosis, and CEUS was used to evaluate the surface morphology of the plaque and the distribution of neovascularization. Postoperatively, pathological sections and immunohistochemical analysis of CD147 and MMP-9 levels in the plaque were performed on the stripped plaque tissue, and the results were analyzed against the CEUS grading and pathological results. Among the 38 patients, pathological results showed that 10 and 28 were in the stable and vulnerable plaque groups, respectively. There were more smokers in the vulnerable plaque group than in the stable plaque group, with higher intraplaques CD147 and MMP-9. The difference in ultrasound plaque surface morphology grading and CEUS grading between the two groups was statistically significant. There was no significant difference in age, sex, incidence of complications such as hypertension, diabetes, and coronary heart disease between the two groups. CD147 was higher in the CEUS grade IV group than in the grades I (P = 0.040) and II (P = 0.010) groups. MMP-9 was higher in the CEUS grade IV group than in the grade II group (P = 0.017); MMP-9 was higher in the grade III group than in the grade II group (P = 0.015). Intraplaque contrast enhancement intensity was positively correlated with CD147 (r = 0.462, P = 0.003) and MMP-9 (r = 0.382, P = 0.018) levels. There was moderate consistency between the assessment of plaque vulnerability by 2D-ultrasound and by histopathological hematoxylin-eosin (HE) (kappa = 0.457, P > 0.05). 2D diagnosis of vulnerable plaque had a sensitivity of 85.7%, a specificity of 60.0%, a positive predictive value of 85.7%, a negative predictive value of 60.0%, and an accuracy of 78.0%. There was a strong consistency between the assessment of plaque vulnerability by CEUS and histopathological HE (kappa = 0.671, P < 0.01). CEUS had a sensitivity of 89.2%, a specificity of 80.0%, a positive predictive value of 92.6%, a negative predictive value of 72.7%, and an accuracy of 86.8% for the diagnosis of vulnerable plaques; CEUS is a reliable, non-invasive test that can show the distribution of neovascularization within vulnerable plaques, evaluate the vulnerability and risk of intraplaque hemorrhage, with a high consistency with pathological findings. The degree of intraplaque enhancement and the levels of CD147 and MMP-9 in the tissue were positively correlated.